2019
DOI: 10.1002/mmce.22108
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐port MIMO dielectric resonator antenna for WLAN applications

Abstract: A dual‐port multiple‐input multiple‐output (MIMO) dielectric resonator antenna (DRA) for 5 GHz IEEE (802.11a/h/j/n/ac/ax) is discussed in this article. Two prototypes of single feed DRA and dual feed MIMO DRA are fabricated and measured results are compared with the simulated data. The proposed single feed DRA and dual feed MIMO DRA exhibits wide impedance bandwidth (IBW). Antennas have been fabricated on Rogers RT Duroid substrate with Eccostock made DRA placed over the substrate. DRAs are excited by aperture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Thanks to the multi‐mode nature of the DP resonator, the bandwidth of the proposed antenna is wider than those of the antenna in References 19,23‐26. Although the antennas in References 21 and22 have a wider bandwidth, their profile is almost seven times that of the proposed antenna. Besides, benefiting from the differential‐fed scheme, the isolation of the proposed antenna is relatively high.…”
Section: Experiments Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thanks to the multi‐mode nature of the DP resonator, the bandwidth of the proposed antenna is wider than those of the antenna in References 19,23‐26. Although the antennas in References 21 and22 have a wider bandwidth, their profile is almost seven times that of the proposed antenna. Besides, benefiting from the differential‐fed scheme, the isolation of the proposed antenna is relatively high.…”
Section: Experiments Results and Discussionmentioning
confidence: 90%
“…The dual-polarized antenna can not only increase the communication channel capacity, but also effectively decrease the mutual interference between the two channels and improve the communication efficiency, [21][22][23][24] which has been widely applied in recent years. For the dual-polarized antenna, achieving high isolation between the two input ports is absolutely critical.…”
Section: Introductionmentioning
confidence: 99%
“…MIMO performance has been evaluated by calculating italicDG=101ECC2 21‐23 and ECC using Equation ). italicECC=||4π[],trueF1(),θϕ*trueF2false(θϕfalse)dnormalΩ24πF1false→θϕ2dnormalΩ4πF2false→(θϕ)2dnormalΩ where trueFi(),θϕ is three dimensional field radiation pattern of the MIMO antenna when port‐ i is excited. Ω is solid angle and * represents the Hermitian product operator.…”
Section: Results and Validationmentioning
confidence: 99%
“…High speed wireless data transfer became possible because of advent of multiple input multiple output (MIMO) technology. Different configurations of MIMO DRA are presented in recent times [10][11][12][13][14][15][16]. In [10] authors reviewed recent MIMO DRAs with various perspective and concluded that multi-port MIMO DRA are tough to design owing to problems associated with them.…”
Section: Introductionmentioning
confidence: 99%
“…In [10] authors reviewed recent MIMO DRAs with various perspective and concluded that multi-port MIMO DRA are tough to design owing to problems associated with them. In [12][13][14][15][16], dual-port, dual-band, four-port and multi-band MIMO DRA for various wireless applications such as 5G, sub-6 GHz, X-band applications have been proposed. In MIMO DRAs as the number of ports increased, complexity and problem of maintaining isolation between feeding ports, also become prominent.…”
Section: Introductionmentioning
confidence: 99%